Novel zinc compound with thiosemicarbazone of glyoxylic acid: Synthesis, crystal structure, and bioactivity properties - YALÇIN, BAHATTİN (ELSEVIER, 2020)
Reaction of zinc nitrate with thiosemicarbazone of glyoxylic acid (H(2)GAT) leads to the formation of the new complex that have been characterized by spectroscopic methods. Crystal structure of the compound Zn3C18H34N18O17S6 (1) was determined using single crystal X-ray diffraction methods. Single crystal X-ray measurements showed that the complex crystallized in a triclinic system with the space group P-1. The structure of complex 1 presents distorted octahedral geometry around the zinc ion centre. In the crystal structure, Zn(II) ion is coordinated by two nitrogen, two oxygen and two sulfur atoms from two different thiosemicarbazone of glyoxylic acid and two oxygen atoms from two different water molecules. Thermogravimetry shows four steps of decomposition in the temperature range 225-990 degrees C. This complex was an inhibitor of butyrylcholinesterase (BChE), cytosolic carbonic anhydride I and II isoforms (hCA I and II) and acetylcholinesterase (AChE) enzymes for complex 1 with Ki values of 0.95 +/- 0.10 mu M for hCA I, 1.54 +/- 0.24 mu M for hCA II, 25.98 +/- 2.44 mu M for BChE, 166.21 +/- 13.63 mu M for alpha-glycosidase and 18.53 +/- 1.36 mu M for AChE, respectively. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Zn-complex; Thiosemicarbazones; Crystal structure; Enzyme inhibition; CARBONIC-ANHYDRASE; BIOLOGICAL-ACTIVITY; 3-AMINOPYRIDINE-2-CARBOXALDEHYDE THIOSEMICARBAZONE; HETEROCYCLIC THIOSEMICARBAZONES; RIBONUCLEOTIDE REDUCTASE; INHIBITORY PROPERTIES; COPPER(II) COMPLEXES; MULTIDRUG-RESISTANCE; ALPHA-GLUCOSIDASE; METAL-COMPLEXES